Anti–Domain I β2-Glycoprotein I Antibodies and Activated Protein C Resistance Predict Thrombosis in Antiphospholipid Syndrome: TAC(I)T Study. (23rd June 2020) - Zuily, Stephane; de Laat, Bas; Guillemin, Francis; Kelchtermans, Hilde; Magy-Bertrand, Nadine; Desmurs-Clavel, Hélène; Lambert, Marc; Poindron, Vincent; de Maistre, Emmanuel; Dufrost, Virginie; Risse, Jessie; Shums, Zakera; et al.
Abstract: Background: Antibodies binding to domain I of β2 -glycoprotein I (aDI) and activated protein C (APC) resistance are associated with an increased risk of thrombosis in cross-sectional studies. The objective of this study was to assess their predictive value for future thromboembolic events in patients with antiphospholipid antibodies (aPL) or antiphospholipid syndrome. Methods: This prospective multicenter cohort study included consecutive patients with aPL or systemic lupus erythematosus. We followed 137 patients (43.5 ± 15.4 year old; 107 women) for a mean duration of 43.1 ± 20.7 months. Results: We detected aDI IgG antibodies by ELISA in 21 patients. An APC sensitivity ratio (APCsr) was determined using a thrombin generation–based test. The APCsr was higher in patients with anti–domain I antibodies demonstrating APC resistance (0.75 ± 0.13 vs 0.48 ± 0.20, P < 0.0001). In univariate analysis, the hazard ratio (HR) for thrombosis over time was higher in patients with aDI IgG (3.31 [95% CI, 1.15–9.52]; P = 0.03) and patients with higher APC resistance (APCsr >95th percentile; HR, 6.07 [95% CI, 1.69–21.87]; P = 0.006). A sensitivity analysis showed an increased risk of higher aDI IgG levels up to HR 5.61 (95% CI, 1.93–16.31; P = 0.01). In multivariate analysis, aDI IgG (HR, 3.90 [95% CI, 1.33–11.46]; P = 0.01) and APC resistance (HR, 4.98 [95% CI, 1.36–18.28]; P = 0.02) remained significant predictors of thrombosis over time. Conclusions: Our study shows that novel tests for antibodies recognizing domain I of β2 -glycoprotein I and functional tests identifying APC resistance are significant predictors of thrombosis over time and may be useful for risk stratification.